Shallow-ocean methane leakage and degassing to the atmosphere: triggered by offshore oil-gas and methane hydrate explorations - Zhang, Yong; Zhai, Wei-Dong (Frontiers in Marine Science, 2015)
Both offshore oil-gas exploration and marine methane hydrate recovery can trigger massive CH4 release from seafloor. During upward transportation of CH4 plume through water column, CH4 is subjected to dissolution and microbial consumption despite the protection of hydrate and oil coating on bubbles surface. The ultimate CH4 degassing to the atmosphere appears to be water-depth dependent. In shallow oceans with water depth less than 100 m, the natural or human-induced leakages or both lead to significant sea-to-air CH4 degassing from 3.00 to 1.36 × 105 μmol m-2 d-1. To quantify the human-perturbation induced CH4 degassing, the combination of top-down modeling and bottom-up calculations is essential due to spatial and temporal variability of diffusion and ebullition at water-air interface.